2017
DOI: 10.20892/j.issn.2095-3941.2017.0033
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation and anticancer drug discovery

Abstract: Cellular growth, development, and differentiation are tightly controlled by a conserved biological mechanism: the cell cycle. This cycle is primarily regulated by cyclin-dependent kinase (CDK)-cyclin complexes, checkpoint kinases, and CDK inhibitors. Deregulation of the cell cycle is a hallmark of the transformation of normal cells into tumor cells. Given its importance in tumorigenesis, several cell cycle inhibitors have emerged as potential therapeutic drugs for the treatment of cancers-both as single-agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(104 citation statements)
references
References 105 publications
2
99
0
3
Order By: Relevance
“…[50] Multiple other studies have shown the role of cell cycle in cancer pathogenesis, and cell cycle regulators are currently being used in the clinic. [51,52]…”
Section: Discussionmentioning
confidence: 99%
“…[50] Multiple other studies have shown the role of cell cycle in cancer pathogenesis, and cell cycle regulators are currently being used in the clinic. [51,52]…”
Section: Discussionmentioning
confidence: 99%
“…Cluster2 was featured by enrichment of the majority of genes including CDK4 ( Figure 7A) and lower expression of nc886 ( Figure 7B). Some cancer drugs target cell cycle genes [23]. For example, palbociclib is an FDA-approved CDK4/6 inhibitor.…”
Section: Therapeutic Implication For Escc With Unfavorable Prognosismentioning
confidence: 99%
“…CDKs are a family of serine/threonine kinases discovered in yeast, classically shown to promote cell-cycle transitions via interaction with various fluctuating cyclins (75,76). A plethora of evidence suggest that the classical cell cycle CDKs, such as CDK1 and CDK2, are targets for treating various malignancies driven by uncontrolled proliferation (77,78). Interfering with CDK function by targeting CDK regulatory kinases upstream of CDK1/2, such as CHK1 (79) and WEE1 kinase (80), or their combination (81), has also shown proof-of-principle activity in AML (79), and other cancers (82).…”
Section: Cdk Inhibitors As Cancer Therapeuticsmentioning
confidence: 99%